Exploring the carbohydrate‐binding ability of Canavalia bonariensis lectin in inflammation models. Issue 11 (9th July 2020) - Cavada, Benildo S.; Silva, Mayara T. L.; Osterne, Vinicius J. S.; Pinto‐Junior, Vanir R.; Lossio, Claudia F.; Madeira, Juliana C.; Pereira, Maria G.; Leal, Rodrigo B.; Ferreira, Wandemberg P.; Nascimento, Kyria S.; Assreuy, Ana M. S.
Abstract: Lectins are a group of proteins of non‐immune origin recognized for their ability to bind reversibly to carbohydrates. Researchers have been intrigued by oligosaccharides and glycoconjugates for their involvement as mediators of complex cellular events and then many biotechnological applications of lectins are based on glycocode decoding and their activities. Here, we report a structural and biological study of a ConA‐like mannose/glucose‐specific lectin from Canavalia bonariensis seeds, CaBo. More specifically, we evaluate the binding of CaBo with α‐methyl‐D‐mannoside (MMA) and mannose‐1, 3‐α‐D‐mannose (M13) and the resultant in vivo effects on a rat model of acute inflammation. A virtual screening was also carried out to cover a larger number of possible bindings of CaBo. In silico analysis demonstrated the stability of CaBo interaction with mannose‐type ligands, and the lectin was able to induce acute inflammation in rats with the participation of the carbohydrate recognition domain (CRD) and histamine release. These results confirm the ability of CaBo to interact with hybrid and high‐mannose N ‐glycans, supporting the hypothesis that CaBo's biological activity occurs primarily through its interaction with cell surface glycosylated receptors.